Product quality and innovation Hungarian firm level data - László Halpern (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Innovation enhances other performance indicators of a firm beside productivity. Buyers are ready to pay higher price for higher quality or more suitable products due to innovation. Product prices, however, reflect the market position of the firm, too. Demand functions estimated using transaction level trade and domestic sales data yield firm level aggregated measure for quality. Productivity, size and foreign ownership increase, while innovation decreases our quality measure. Deeper analysis of innovation is needed in order to understand the reason for these seemingly contradicting results.
Keywords: F14; L15; L25; 330; trade; quality; scope; innovation